Sistema gerenciador de documentos para a entidade social Casa do Piá - Corrêa, Gustavo Macias (2022)
Social entities are important because they offer social assistance services to the neediest, and these institutions are monitored by the National Council of Social Assistance, and by the Municipal Council of Social Assistance (CMAS) of their municipality. In order to maintain the registration of the social entity with the CMAS, it is necessary to deliver documents, control attendance and technical or psychological reports on the users served. These documents were made manually by the institution's social worker and then the data were transferred to the document on the computer to be printed. In addition to being cumbersome, there is a problem with the privacy of these documents, which contain sensitive data. The objective of this work was to develop a Desktop application to simplify and speed up the process of creating documents and reports. The work focuses on the generation of documentation for Casa do Piá, a social entity in the municipality of Ponta Grossa - PR, along with the necessary documentation for the development and maintenance of the software. The product of this work was a software developed in Java that performs the control of activities related to children and young people served by the institution. During the development, popular tools and frameworks in the job market were used, such as Spring, Hibernate and Gradle, in addition to the graphical interface in JavaFX. The intention is that it can help in the administration of the entity's users, as well as in the reduction of the work time dedicated to the preparation of documents that must be sent to CMAS.